A Developmental Analysis of Cognitive/Metacognitive Skills in Male and Female Students in Mashhad - Bori, Mahboobeh; Karimzadeh, Mansoureh; Mousazadeh, Zohreh (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The present study aimed to compare cognitive and metacognitive skills among students in Mashhad. Methods and Materials: This research employed a non-experimental comparative design. The statistical population comprised male and female students in two age groups (10–12 and 13–15 years) from the seven districts of Mashhad in 2023, totaling 4,618 students. The sample size was determined using Cochran's formula, resulting in a sample of 355 students, who were selected through multi-stage cluster sampling. Data were collected using the Cognitive and Metacognitive Strategies Questionnaire by Dawson and McInerney (2004). Independent sample t-tests and multivariate analysis of variance (MANOVA) were used to analyze the data and test the research hypotheses. Findings: According to the findings, significant differences were observed between the studied age groups in all components of metacognitive skills (planning, monitoring, and regulation) and cognitive skills (semantic elaboration, rehearsal and practice, and organization). Students aged 13–15 had higher mean scores in cognitive and metacognitive skills compared to students aged 10–12. Conclusion: Based on the results, cognitive and metacognitive skills increase with age in students.